Colistin-Induced Nephrotoxicity, A major risk after cardiopulmonary bypass - Data - Shajahan Idayathulla (19872639) (2024)
This retrospective study evaluates the incidence of Colistin - induced nephrotoxicity in 36 patients who underwent cardiac surgery with cardiopulmonary bypass (CPB) and received Colistin for at least 72 hours. Conducted over three years the study emphasizes the elevated risks of nephrotoxicity and mortality linked to Colistin use in this high-risk population. Other Information License: http://creativecommons.org/licenses/by/4.0/